KAJIAN KONSTITUSI SEBAGAI LANDASAN DASAR TERHADAP PENYELENGGARAAN PEMILU DI INDONESIA - Anwar Hidayat (Jurnal Hukum Mimbar Justitia, 2019)
Regarding the electoral system explained that the recruitment of a candidate by a political party depends on the electoral system that develops in a country. An open list allows a candidate to get For political parties, the popularity of a candidate makes voter choices focused on his party rather than on other political parties. In Indonesia too, the latest election law requires each political party to include a minimum of 30% female candidates. This opens up greater possibilities for women to become legislators. However, on the other hand political parties are very selective towards women candidates: Only women candidates who meet certain criteria (beautiful, popular, academic) actually make up 30% of their party candidates. In scientific writing, the writer uses the method of normative juridical approach, with research specifications namely descriptive analysis. Research locations on the Buana Perjuangan University campus Karawang The results of the study discussed the 1955 Election System to the 2019 Election System and the great ideals of the intention to hold simultaneous elections in 2019 one of which was to strengthen the Presidential System. Concurrent elections can be one of the efforts to reform the Presidential system implemented in Indonesia after the reform.Â Keywords: Constitution; Elections; Political System.